“Penzotti’s Pathways”. Protestant Missions in South America and the Building of Secularism - Paula Seiguer (Iberoamericana. América Latina - España - Portugal, 2019)
This article looks into the case of Francisco Penzotti, a methodist missionary who suffered a nine-month imprisonment in Peru between 1889 and 1891 because of his preaching. It analyzes not only what happened to Penzotti but the uses that the press and protestant literature made of it: in effect, it tries to show how and why this episode turned into “a case” and what it can tell us about the ways in which protestants sought to implant their faith in South America, about their self-perception, about their ties with local elites and foreign powers and about the link between the introduction of Protestantism in the sub-continent and the building of a secular state.